Predictive parameter of tolvaptan effectiveness in cirrhotic ascites. Issue 9 (9th November 2016) - Kawaratani, Hideto; Fukui, Hiroshi; Moriya, Kei; Noguchi, Ryuichi; Namisaki, Tadashi; Uejima, Masakazu; Kitade, Mitsuteru; Takeda, Kosuke; Okura, Yasushi; Kaji, Kosuke; Nishimura, Norihisa; Takaya, Hiroaki; et al.
Abstract : Aims: The efficacy of the vasopressin V2 receptor antagonist tolvaptan for difficult‐to‐treat cirrhotic ascites has recently been reported. However, its effect is variable among patients. This study aimed to clarify the predictive factors for obtaining a good response to tolvaptan in patients with difficult‐to‐treat ascites. Methods: Data were collected from 50 patients with liver cirrhosis having ascites (hepatitis B, n  = 1; hepatitis C, n  = 22; alcoholism, n  = 11; and others, n  = 16) after treatment with tolvaptan (3.75–7.5 mg/day) in addition to conventional diuretics. A follow‐up assessment was carried out after 7‐day tolvaptan treatment for all patients. Results: After an uneventful 7‐day tolvaptan treatment, 18 patients (36.0%) lost more than 2 kg of their body weight (responders). Twenty‐six patients (52.0%) showed an increase in urine volume (>300 mL) on day 2. Tolvaptan was also effective for patients with pleural effusion, portal vein thrombosis, and hepatocellular carcinoma. Basal blood urea nitrogen (BUN) levels, plasma renin activity, and aldosterone levels were significantly higher in the poor responders (<2 kg weight loss), who were considered to be in the relative vascular underfilling state, than in the responders. Basal BUN was extracted as a predictive factor of responsiveness by multivariate logistic regression analysis. Conclusions: Tolvaptan is useful and safe for the treatment of cirrhotic ascites. This report showed that BUN will predict the response of tolvaptan even when measured before tolvaptan treatment.